Electrólisis aplicada para la Remoción de Hierro y Zinc en Drenaje Ácido de Mina - Farfán Chilicaus, Gary Christiam; Fajardo-Flores, Rut K.; Licapa-Redolfo, Gladys S.; Licapa-Redolfo, Rolando (LACCEI, 2023)
The objective of this study was to determine, by means of electrolysis, the influence of current density and time on the removal of total iron and zinc from acid mine drainage of Hualgayoc mining environmental liabilities. Electrolysis is an alternative method that can effectively remove ionic metals. The crude acid mine drainage was characterized by total metal analysis, yielding an initial total iron concentration of 1788.76 mg/l, an initial total zinc concentration of 196.51 mg/l, and a pH of 4.11. For the levels of each variable analyzed, 4 levels and 3 repetitions were determined for a total of 51 samples as well as the initial blank, obtaining the best results using a current density of 40 mA/cm2 and a time of 120 minutes, resulting in a final concentration of 1.98 mg/L of total iron, 1.16 mg/L of total zinc and pH 8.5. The technology removed 99.89% of the iron and 99.41% of the zinc.